Electrospinning of Octenylsuccinylated Starch-Pullulan Nanofibers from Aqueous Dispersions. (15th April 2021) - Li, Songnan; Kong, Lingyan; Ziegler, Gregory R.
Highlights: Starch-based nanofibers successfully electrospun from aqueous dispersions Addition of pullulan aided in electrospinning of octenylsuccinylated (OS) starch Electrospinnability of OS starches dictated mainly by rheological properties Spinnability map of OS starch and pullulan established Abstract: We aimed to develop a greener process for dry-electrospinning food-grade modified starch through the elimination of organic solvents. The rheological properties and electrospinnability of aqueous dispersions of commercial octenylsuccinylated (OS) starches with various molecular weight (Mw) were investigated, yet only nanofibers with beads or defects could be obtained from OS starch with the highest Mw, i.e., Purity Gum @ Ultra (PGU). Further improvement in the fiber morphology was achieved by adding pullulan (PUL) as a minor component in the spinning dope. Smooth, continuous, and bead-free nanofibers (147-250 nm) were obtained from the PGU-PUL dispersions. Shown on an electrospinnability map, the successful electrospinning of 12%, 15%, and 20% (w/v) aqueous PGU dispersions required a minimum addition of 6%, 5%, and 3% (w/v) of PUL, respectively. The addition of PUL contributed to establishing sufficient molecular entanglement for electrospinning. This study provides a promising green process to produce starch-based nanofibers for use in various applications, e.g., drug delivery, wound dressing, and tissue engineering.